High Efficacy but Low Potency of δ-Opioid Receptor-G Protein Coupling in Brij-58-Treated, Low-Density Plasma Membrane Fragments - Roubalova, Lenka; Vosahlikova, Miroslava; Brejchova, Jana; Sykora, Jan; Rudajev, Vladimir; Svoboda, Petr (PloS one, 2015)
PRINCIPAL FINDINGS: HEK293 cells stably expressing PTX-insensitive δ-opioid receptor-Gi1α (C351I) fusion protein were homogenized, treated with low concentrations of non-ionic detergent Brij-58 at 0°C and fractionated by flotation in sucrose density gradient. In optimum range of detergent concentrations (0.025-0.05% w/v), Brij-58-treated, low-density membranes exhibited 2-3-fold higher efficacy of DADLE-stimulated, high-affinity [32P]GTPase and [35S]GTPγS binding than membranes of the same density prepared in the absence of detergent. The potency of agonist DADLE response was significantly decreased. At high detergent concentrations (>0.1%), the functional coupling between δ-opioid receptors and G proteins was completely diminished. The same detergent effects were measured in plasma membranes isolated from PTX-treated cells. Therefore, the effect of Brij-58 on δ-opioid receptor-G protein coupling was not restricted to the covalently bound Gi1α within δ-opioid receptor-Gi1α fusion protein, but it was also valid for PTX-sensitive G proteins of Gi/Go family endogenously expressed in HEK293 cells. Characterization of the direct effect of Brij-58 on the hydrophobic interior of isolated plasma membranes by steady-state anisotropy of diphenylhexatriene (DPH) fluorescence indicated a marked increase of membrane fluidity. The time-resolved analysis of decay of DPH fluorescence by the "wobble in cone" model of DPH motion in the membrane indicated that the exposure to the increasing concentrations of Brij-58 led to a decreased order and higher motional freedom of the dye. SUMMARY: Limited perturbation of plasma membrane integrity by low concentrations of non-ionic detergent Brij-58 results in alteration of δ-OR-G protein coupling. Maximum G protein-response to agonist stimulation (efficacy) is increased; affinity of response (potency) is decreased. The total degradation plasma membrane structure at high detergent concentrations results in diminution of functional coupling between δ-opioid receptors and G proteins.
Keywords: Hydrophobic and Hydrophilic Interactions; pertusový toxin; Temperature; Pertussis Toxin; HEK293 buňky; hydrofobní a hydrofilní interakce; vztah mezi dávkou a účinkem léčiva; HEK293 Cells; cetomakrogol; Cell Membrane; lidé; Detergents; Humans; buněčná membrána; teplota; Dose-Response Relationship, Drug; Receptors, Opioid, delta; Cetomacrogol; receptory opiátové delta; detergenty